Figuring Things Out: Contemplating Drug Addiction and Disclosure In and Out of the Field. (September 2022) - Revier, Kevin
From 2017 to 2019, I conducted fieldwork on the opioid crisis in upstate New York. As part of my research, I interviewed people who use/d opioids. Interviewees discussed their beginning use, escalating use, and, for many, eventual sobriety. Throughout research, I reflected on my own drug consumption and attempts at moderation and abstinence—mostly regarding my heavy use of alcohol. I tracked my reflections in a field diary, writing over 200 entries. Yet, like many ethnographers, I extracted the notes out of my final research write-up. In part, my lack of disclosure was perhaps due to my being in what James Prochaska and Carlo DiClemente refer to as the contemplation stage of change: I was unsure how to identify myself as a person who uses/struggles with drugs and alcohol, and I was not ready to commit to long-term sobriety. Whether I disclosed or not, such contemplation did affect my fieldwork: it shaped my motivation to pursue drug research and advocacy; my relationships and interactions with participants; and ways I navigated harm reduction and sober support spaces. After over 2 years of being out of the field (and now in a state of long-term sobriety), I revisit my field diary through autoethnographic exploration. In doing so, I place contemplation within the growing conversation on reflexivity and disclosure in critical drug studies.